The Feitao ritual: masquerading between divine and secular ethos in the Maonan cosmos - Yixing, Liu; Ow, Wei Chow (Common Ground Research Networks, 2024)
The Feitao ritual [肥套仪式] is a religious performance of the Maonan ethnic group [毛南族] in China. It has been challenged in its role as a traditional religion under the globalized phenomenon of heritagization, state intervention, and commercial investment. Contemporary interpretations of the Feitao ritual have become a purified and re-imagined expression of renowned Maonan cultural heritage, striving to find a balance between commodification and heritage preservation. This article analyzes the function of masks in the ritual, which not only symbolizes a connection with the divine but is also instrumental in the interaction between the divine and secular worlds. Masks as part of the ritual undergo a dynamic process of transformation of divine religious practices into secular performances. The authors support the notion of preserving the religious essence of the Feitao ritual in practical and constructive ways, as they observe its tenacious role in radiating the divinity of the community’s beliefs and blessing for the sustainability of the Maonan’s religious lineage in the secular world.